A landscape review with novel criteria to evaluate microbial drivers for cancer: priorities for innovative research targeting excessive cancer mortality in sub-Saharan Africa - van Dorsten, Rebecca Toumi; Breiman, Robert F. (Frontiers in Cellular and Infection Microbiology, 2025)
The escalating cancer burden in Sub-Saharan Africa (SSA), with projected doubling of incidence and mortality by 2040, necessitates innovative, cost-effective strategies for prevention, diagnosis, and treatment. While known infectious triggers like HPV, hepatitis viruses, and H. pylori account for an estimated 28.7% of cancers in SSA, the full scope of microbially-mediated oncogenesis remains underexplored. We examine existing data and formulate plausible hypotheses regarding the potential roles of additional infectious agents in cancer development within SSA. We explore mechanisms through which microbes may directly or indirectly contribute to oncogenesis, including the action of viral oncogenes, induction of chronic inflammation, mutational signatures, and the impact of immunosuppression, particularly in the context of HIV. Potential microbial triggers warrant further investigation, such as viruses (MMTV, CMV, polyomaviruses, SARS-CoV-2), bacteria (Fusobacterium nucleatum, Cutibacterium acnes, Salmonella Typhi), fungi (Candida, Aspergillus), parasites (Schistosoma japonicum and mansoni and Toxoplasma gondii) and the complex interplay with the microbiome. Given the significant challenges in establishing causation for microbial facilitators of cancer, with traditional postulates showing limited utility, we propose a refined set of criteria tailored to microbial oncogenesis, aiming to guide future research efforts. These criteria incorporate elements of both Koch’s postulates and the Bradford Hill framework, adapted to address the unique characteristics of microbial interactions with human hosts. By leveraging existing knowledge and plausible causal relationships, and by implementing advanced experimental tools such as next-generation sequencing and multi-omics analyses, coupled with machine learning approaches and collaborative, multidisciplinary research, we propose to accelerate the identification of novel microbial links to cancer. This knowledge may pave the way for targeted interventions such as new approaches for screening and diagnosis, and strategies for prevention including vaccine development or modification of existing vaccines (or recommendations for immunization timing and population targets). While acknowledging the inherent complexities of studying polymicrobial interactions and the challenges of translating in vitro findings to human populations, this work aims to provide a framework for future research and intervention strategies to reduce the escalating cancer burden and address global inequities in SSA. The ultimate goal is to inform evidence-based public health policies and clinical practices that will improve cancer outcomes in this vulnerable region.